A new narrower circumscription and a nomenclatural synopsis for Calea subg. Meyeria (Asteraceae: Neurolaeneae) - Bueno, Vinicius R.; Reis-Silva, Genilson A.; Nakajima, Jimi N.; Goste, Morgan R.; Heiden, Gustavo (Phytotaxa, 2025)
The studies on Calea subg. Meyeria (Neurolaeneae, Asteraceae), a group from open vegetation in Southeastern South America, recently resulted in the description of novel species and nothospecies. Continued progress on the nomenclatural and taxonomic studies of this subgenus is presented here. A comprehensive bibliography for species described in this section was compiled and revised to allow the proposition of nomenclatural changes. All type specimens were consulted either in person or using high-resolution digital images. Based on these efforts, we propose a narrower circumscription of Calea subg. Meyeria, altering the number of accepted taxa assigned to it from 15 to 9. The subgenus is here proposed to be characterized morphologically by shrubs with a cymose capitulescence, capitula with four or more foliaceous outer phyllaries and cypsela longer than the pappus. As here defined, it comprises eight species (C. funkiana, C. marginata, C. myrtifolia, C. parvifolia, C. phyllolepis, C. pruskiana, C. subintegerrima, and C. triantha) and one nothospecies (C. × parviantha). Altogether, we synonymize four names; propose lectotypifications for two names; recognize three new isolectotypes; and provide corrections for type specimen collection data from six taxa, including collector names, collection date, and locality.